Genome-Wide Analysis of miRNA-mRNA Interactions in Marrow Stromal Cells. (19th February 2014) - Balakrishnan, Ilango; Yang, Xiaodong; Brown, Joseph; Ramakrishnan, Aravind; Torok-Storb, Beverly; Kabos, Peter; Hesselberth, Jay R.; Pillai, Manoj M.
Abstract : Regulation of hematopoietic stem cell proliferation, lineage commitment, and differentiation in adult vertebrates requires extrinsic signals provided by cells in the marrow microenvironment (ME) located within the bone marrow. Both secreted and cell-surface bound factors critical to this regulation have been identified, yet control of their expression by cells within the ME has not been addressed. Herein we hypothesize that microRNAs (miRNAs) contribute to their controlled expression. MiRNAs are small noncoding RNAs that bind to target mRNAs and downregulate gene expression by either initiating mRNA degradation or preventing peptide translation. Testing the role of miRNAs in downregulating gene expression has been difficult since conventional techniques used to define miRNA-mRNA interactions are indirect and have high false-positive and negative rates. In this report, a genome-wide biochemical technique (high-throughput sequencing of RNA isolated by cross-linking immunoprecipitation or HITS-CLIP ) was used to generate unbiased genome-wide maps of miRNA-mRNA interactions in two critical cellular components of the marrow ME: marrow stromal cells and bone marrow endothelial cells. Analysis of these datasets identified miRNAs as direct regulators of JAG1, WNT5A, MMP2, and VEGFA; four factors that are important to ME function. Our results show the feasibility and utility of unbiased genome-wide biochemical techniques in dissecting the role of miRNAs in regulation of complex tissues such as the marrow ME. Stem Cells   2014;32:662–673